2013
DOI: 10.1016/j.physbeh.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Prior access to a sweet is more protective against cocaine self-administration in female rats than in male rats

Abstract: It is well established that female rats are more sensitive than male rats to the reinforcing effects of cocaine (Lynch, 2008 for review). We hypothesized that greater preference for cocaine would support greater avoidance of a cocaine-paired taste cue in female vs. male rats. Moreover, at least in male rats, greater avoidance of the taste cue is associated with greater cocaine self-administration (Grigson & Twining, 2002). Thus, we anticipated that female rats would not only demonstrate greater avoidance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 75 publications
3
27
0
Order By: Relevance
“…On the other hand, it is possible that sensitivity to sweet rewards could be a protective factor against drug abuse in females. A recent animal study tested this possibility by assessing consumption of a saccharine cue that signaled subsequent access to cocaine (Cason and Grigson 2013). The authors found that females consumed more of the saccharine cue and less subsequent cocaine, whereas males avoided the saccharin cue and consumed greater amounts of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is possible that sensitivity to sweet rewards could be a protective factor against drug abuse in females. A recent animal study tested this possibility by assessing consumption of a saccharine cue that signaled subsequent access to cocaine (Cason and Grigson 2013). The authors found that females consumed more of the saccharine cue and less subsequent cocaine, whereas males avoided the saccharin cue and consumed greater amounts of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral factors such as dose of drug, length of access, and even pair-housing (Westenbroek et al 2013) or prior access to sweets (Cason and Grigson 2013) may be integral to the development of sex differences in cocaine acquisition. A biological basis for cocaine acquisition has been suggested by Hu and colleagues (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have identified a number of factors that affect avoidance of a drug-paired cue and/or responding for drug. For example, female Sprague-Dawley rats exhibit more acceptance of a cocaine-paired saccharin cue and less cocaine self-administration in the taste-drug model than male rats (Cason & Grigson, 2013). Environmental enrichment during adulthood reduces acquisition of cocaine self-administration in male rats (Puhl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%